Economical Investigation of green hydrogen supply for Hydrogen-Powered ship by Off-Grid wave and wind energy hubs - Sarina Kheirani; Ali Houmani; Mohammad Hossein Jahangir (Energy Conversion and Management: X)
Given the desire of maritime industry to reduce pollutant emissions and extensive use of hydrogen as an energy carrier, this study explores one possibility. Wave energy is considered as the principal energy source together with wind energy to meet energy needs of hydrogen ships. Using wave energy to provide marine hydrogen has never been done, specifically the economic aspect of it. The optimal configuration for a hydrogen refueling infrastructure is investigated, considering the limitations of a low-potential resource area and the demands of a large hydrogen powered ship. Three hypothetical stops located between two major bays and powered by a combination of wave and wind energy maximize hydrogen production efficiency. Economic outcomes are reviewed and presented from multiple perspectives to ensure reasonable hydrogen production and consumption over a 20-year project life. Levelized cost of hydrogen is best at 2.09$ per kilogram, significantly below the typical price of 3–6$ for initial capital cost of 162$M modeled hybrid system.